Neonatal Death Incidence in Healthcare Facility in Indonesia: Does Antenatal Care Matter? - Masruroh1,2, Ah Yusuf3 , Nikmatur Rohmah4, Irfansyah Baharudin Pakki5 , Anita Dewi Prahastuti Prasoj (Institute of Medico-legal Publications Pvt Ltd, 2021)
Despite having carried out maternity care in healthcare facilities, neonatal deaths still occur. A study wasconducted to analyze the effect of antenatal care (ANC) on neonatal death incidence in healthcare facilitiesin Indonesia. The study used the 2017 IDHS data. With stratification and multistage random sampling,13.104 women aged 15-49 years with live births in the last 5 years, who performed maternity care in thehealthcare facility, were sampled. Apart from ANC, other independent variables analyzed were a type ofplace, age, education, wealth, employment, parity, and complication during pregnancy. The final stageemployed a binary logistic regression test. The analysis found that women who made complete ANC visitsduring pregnancy (?4 times) were 0.486 times more likely than women who did not complete ANC visits(<4 times) (OR 0.486; 95% CI 0.266-0.887). The results of this analysis inform that carrying out a completeANC visit is a protective factor for women who perform maternity care in healthcare facilities in Indonesiafrom neonatal death incidence. Apart from ANC, 2 variables were also found to have a significant effecton neonatal death incidence in healthcare facilities in Indonesia. These two variables are the age groupand complications during pregnancy. Meanwhile, education level, wealth status, employment status, andparity proved insignificant. It was concluded that ANC is a determinant of neonatal death incidence inthe healthcare facility in Indonesia. Complete ANC visits are a protective factor for women who performmaternity care in healthcare facilities in Indonesia from neonatal death incidence.